Clinical Needs Finding: Developing the Virtual Experience, A Case Study - Mittal, Vaishali (2013)
We describe an innovative program at the University of California, Davis for students to engage in clinical needs finding. Using a team-based approach, students participated in clinical rotations to observe firsthand the needs of clinicians at the university affiliated medical center. The teams were asked to develop documentary-style videos to capture key experiences that would allow future viewers to use the videos as “virtual” clinical rotations. This was conceived as a strategy to allow students in prohibitively large classes, or students in programs at institutions without associated medical or veterinary school programs, to experience clinical rotations and perform needs assessments. The students' perspectives on the experience as well as instructor analysis of best practices for this type of activity are presented and discussed. We found that the internship experience was valuable to the students participating, by not only introducing the practice of needs finding but for increasing the students' confidence in the practice of engineering design and their ability to work independently. The videos produced were of such high quality that instructors from other institutions have requested copies for instructional use. Virtual clinical rotations through video experiences may provide a reasonable substitute for students who do not have the ability to participate in rotations in person.